Wieczne Jeruzalem vs ziemski Babilon. Wyobrażenie miasta i conditio humana - Nieszczerzewska, Malgorzata (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2018)
The main inquiry of the article is a question of anti-modern and anti-urbanimagery of a 19th century metropolis, that was a reaction to the rapid changes of a moderncity space and culture (both in its physical and spiritual dimension). This imagerywas constructed first and foremost by people, who were attached to tradition, conservativevalues and Christian belief, therefore, the author pays particular attention to theopposition of two, dichotomic urban metaphors: Jerusalem and Babylon, which symbolize not only a materialistic and social sphere of a modern city, but – considered froma perspective of the Christian vision of culture – a condition of human being as well.